2016
DOI: 10.18203/2349-3933.ijam20163734
|View full text |Cite
|
Sign up to set email alerts
|

To evaluate the role of plasma vitamin D level as a prognostic marker and its relation to in-hospital complications in patients with acute coronary syndrome

Abstract: Background: Deficiency in 25-hydroxyvitamin D (25[OH] D), the main circulating form of vitamin D in blood, could be involved in the pathogenesis of acute coronary syndromes (ACS). To date, however, the possible prognostic relevance of 25 (OH) D deficiency in ACS patients remains poorly defined. The purpose of this study was to assess the association between 25 (OH) D levels, at hospital admission, with in-hospital complications in an unselected cohort of ACS patients. Methods: We measured 25 (OH) D in 200 ACS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The study showed that 51% patients had adverse in-hospital outcome; 71.1% patients with low vitamin-D level had adverse inhospital outcome whereas 14.3% patients with normal vitamin-D level had adverse in-hospital outcome with significant association (p<0.001). Kumar, et al, (2016) showed that the patients with vitamin D deficiency were associated with a higher risk for several in-hospital MACEs, including mortality and it was statistically significant (p-value<0.05) 29 .The study supports the close association between low vitamin D levels at hospital presentation and worse prognosis in ACS patients 29 . Indeed, patients with 25 (OH) D deficiency had a 3-fold higher mortality risk, even after adjustment for important independent variables associated with mortality in ACS 29 .…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…The study showed that 51% patients had adverse in-hospital outcome; 71.1% patients with low vitamin-D level had adverse inhospital outcome whereas 14.3% patients with normal vitamin-D level had adverse in-hospital outcome with significant association (p<0.001). Kumar, et al, (2016) showed that the patients with vitamin D deficiency were associated with a higher risk for several in-hospital MACEs, including mortality and it was statistically significant (p-value<0.05) 29 .The study supports the close association between low vitamin D levels at hospital presentation and worse prognosis in ACS patients 29 . Indeed, patients with 25 (OH) D deficiency had a 3-fold higher mortality risk, even after adjustment for important independent variables associated with mortality in ACS 29 .…”
Section: Resultsmentioning
confidence: 54%
“…Kumar, et al, (2016) showed that the patients with vitamin D deficiency were associated with a higher risk for several in-hospital MACEs, including mortality and it was statistically significant (p-value<0.05) 29 .The study supports the close association between low vitamin D levels at hospital presentation and worse prognosis in ACS patients 29 . Indeed, patients with 25 (OH) D deficiency had a 3-fold higher mortality risk, even after adjustment for important independent variables associated with mortality in ACS 29 . In our study, heart failure was significantly higher in patients with low vitamin D level than patients with normal vitamin D level with significant association (p<0.001).…”
Section: Resultsmentioning
confidence: 54%
“…Another study supported those observations and indicated that vitamin D was independently related to mortality at levels below the population median [ 139 ]. In addition, the left ventricular function was more severely compromised in deficient patients [ 140 ]. Furthermore, the diabetic patients with 25(OH)D deficiency had more extensive coronary lesions [ 141 ].…”
Section: Vitamin Dmentioning
confidence: 99%